Effect of dietary protein level on carcass traits and meat properties of Cinta Senese pigs. (28th August 2014) - Sirtori, F.; Crovetti, A.; Acciaioli, A.; Pugliese, C.; Bozzi, R.; Campodoni, G.; Franci, O.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of this study was to test the effect of various dietary protein contents (CP) on the carcass traits and the meat quality of Cinta Senese pigs. A total of 60 Cinta Senese pigs were equally distributed in four dietary groups that were balanced for sex (barrows and gilts) and live weight. The animals in the groups were fed one of four diets (80CP, 100CP, 130CP and 160CP) containing different CP contents (80, 100, 130 and 160 g/kg, respectively). The diets were administered to the pigs during the entire growing–fattening period in a controlled dose of 90 g/kg W0.75, to a maximum of 2.5 kg/day per animal. The duration of the trial was 250 days, ending when the animals reached the target slaughter weight of 145 kg. The 80CP diet produced fatter carcasses than did the other diets; no differences in carcass composition were found among the animals fed the other three diets (total lean cuts: 57.4%, 61.4%, 60.8% and 61.3% for 80CP, 100CP, 130CP and 160CP diet, respectively). The sample joint composition confirmed the highest fatness and the lowest meatiness of pigs fed 80CP. This same pattern was evident for the composition of the muscle (Longissimus lumborum) containing the largest amount of i.m. fat, and the lowest protein content in the 80CP group. Moreover, the 80CP diet resulted in the lightest and yellowest meat with the highest cooking loss. A principal component analysis of the physical and chemical traits of the meat revealed three first factors that explained 56% of the total variance. Among them, only the intersection of Factor1, which combined mainly lower pH at 24 h postmortem and higher drip loss, cooking loss, lightness and yellowness, with Factor2, which associated higher toughness, higher protein and lower fat content, graphically appeared to discriminate the 80CP diet from the other ones. In conclusion, a diet with 80 g/kg of CP content was inadequate for this local breed, while, in consideration of the cost of protein feed and the need to reduce N pollution, the 100CP diet would be an optimal compromise for the growth–fattening of Cinta Senese pigs.